ANALYSIS OF DADIH AS A TRADITIONAL CUISINE SUPPORTING CULINARY TOURISM IN WEST SUMATRA - Mandalia, Siska (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Culinary is an inseparable part of tourist destinations because culinary is one of the basic human needs. Even culinary can be a special attraction when visiting a tourist destination. West Sumatra is one of the provinces that has many advantages, especially in its traditional cuisine. One example is Dadih (Dadiah in the Minangkabau language) which is made from fermented buffalo milk. The objectives of this research are: 1 To identify as a traditional culinary supporting tourism in West Sumatra, 2 Identify the problems faced in the process of developing Dadih as a traditional culinary supporting tourism in West Sumatra, 3 Efforts that can be made in developing Dadih as a traditional culinary supporting tourism in West Sumatra. This research uses a qualitative approach using the literature study method of several writings in journals, articles, and documents related to analyzing traditional culinary in supporting the tourism business. The results of this study indicate that Dadih has the potential to support tourism in West Sumatra as a traditional cuisine.